Considerations of Mutual Exchange in Prosocial Decision-Making - Allidina, Suraiya; Arbuckle, Nathan L.; Cunningham, William A. (Frontiers in Psychology, 2019)
Research using economic decision-making tasks has established that direct reciprocity plays a role in prosocial decision-making: people are more likely to help those who have helped them in the past. However, less is known about how considerations of mutual exchange influence decisions even when the other party’s actions are unknown and direct reciprocity is therefore not possible. Using a two-party economic task in which the other’s actions are unknown, study 1 shows that prosociality critically depends on the potential for mutual exchange; when the other person has no opportunity to help the participant, prosocial behavior is drastically reduced. In study 2, we find that theories regarding the other person’s intentions influence the degree of prosociality that participants exhibit, even when no opportunity for direct reciprocity exists. Further, beliefs about the other’s intentions are closely related to one’s own motivations in the task. Together, the results support a model in which prosociality depends on both the social conditions for mutual exchange and a mental model of how others will behave within these conditions, which is closely related to knowledge of the self.